Hypokalemic periodic paralysis: an unusual presentation - Ramineni, Hari Babu; M, Chandini; M, Sri Vidya; Rakesh, Yerramaneni; S, Vidyadhara (International Journal of Advances in Medicine, 2017)
Hypokalaemia Periodic paralysis is a heterogeneous group of muscle disorder with episodic, short-lived, and hypo-reflexic skeletal muscle weakness, without loss of consciousness and with or without myotonia but without sensory deficit. We report a rare autoimmune disorder in a 23year male patient who had presented with complaints of weakness of both lower limbs since 1 day which is of sudden onset. He was unable to move limbs or walk or climb up stairs. Based on symptoms and laboratory investigations he was diagnosed with Hypokalaemia Periodic Paralysis. Therapy was primarily started with potassium supplements.